A Culture-Based English Approach: Students’ Perception of Developing Speaking Ability - Saiful Anwar; Rizki Nurfida Pambayun; Khoiriyah Shofiyah Tanjung (The Art of Teaching English as a Foreign Language (TATEFL), 2025)
The perception of the students affects their attitude, willingness, motivation, and engagement in classroom activities. Speaking is considered quite challenging to develop by the EFL students among the other language skills. A culture-based English Approach is one of the solutions to overcome that. Therefore, this study aims to explore students’ perceptions of a culture-based English approach in developing their speaking ability. The researcher used a Qualitative descriptive method in the form of a questionnaire and interview data. The participants of this study were 25 undergraduate students in one of the universities in Banyuwangi. Then, the questionnaire was analyzed using a Likert scale, with the formula P = F/N × 100%. The interview data were systematically coded, with specific statements analyzed and categorized into themes that reflected the phenomenon under investigation. The result of the questionnaire shows that almost 80% students give a positive perception of CBE as an Approach to developing speaking ability. The result of the interview shows that the average student's response stated that students have a good perception about the CBE Approach used in speaking, then 26,8% is neutral. Based on both the questionnaire and interview results, we can conclude that CBE gives a positive perception in developing speaking ability.